The Relationship of Workload and Job Stress with Work Fatigue in Factory Employees - Putri Rahmasari, Nelsa; Wibowo, Pipid Ari; Abidin , Zaenal; Ramadhanityas , Karina Nur (Journal La Medihealtico, 2024)
Work fatigue will reduce performance and increase work errors, workers who come in and out of the cracker factory because the salary they get is quite small for workers, the majority of whom have married and have dependents in the family, this is supported by the salary slip shown by the worker to the researcher. The aim of this research is to determine the relationship between workload and work stress with work fatigue in cracker factory employees in Dolopo District. The research method used is quantitative research. This research uses a cross-sectional study design. Researchers determined that the population came from employees of the cracker factory in Dolopo District, Kab. Madiun with a total of 69 workers, the sample size required for cracker factory employees in Dolopo District, Kab. In Madiun, 60 respondents will be researched. Most of the workers at the cracker factory in Dolopo sub-district experience severe work fatigue and work stress. There is a significant relationship between fatigue and work stress among workers at the cracker factory in Dolopo sub-district. The suggestion that the cracker factory needs to make is to make stress management strategies for workers to minimize fatigue and work stress, for example by conducting outbound events or gatherings between workers. Meanwhile, the advice that workers can do is to do muscle stretching or light exercise periodically while working.